High performance simulations of a single X-pinch - Skoulakis, A.; Koundourakis, G.; Ciardi, A.; Kaselouris, E.; Fitilis, I.; Chatzakis, J.; Bakarezos, M.; Vlahakis, N.; Papadogiannis, N. A.; Tatarakis, M.; Dimitriou, V. (IOP, 2022)
The dynamics of plasmas produced by low current X-pinch devices are explored. This comprehensive computational study is the first step in the preparation of an experimental campaign aiming to understand the formation of plasma jets in table-top pulsed power X-pinch devices. Two state-of-the-art magneto-hydro-dynamic codes, GORGON and PLUTO, are used to simulate the evolution of the plasma and describe its key dynamic features. GORGON and PLUTO are built on different approximation schemes and the simulation results obtained are discussed and analyzed in relation to the physics adopted by each code. Both codes manage to accurately handle the numerical demands of the X-pinch plasma evolution and provide precise details on the mechanisms of the plasma expansion, the jet-formation, and the pinch generation. Furthermore, the influence of electrical resistivity, radiation transport and optically thin losses on the dynamic behaviour of the simulated X-pinch produced plasma is studied in PLUTO. Our findings highlight the capabilities of the GORGON and PLUTO codes in simulating the wide range of plasma conditions found in X-pinch experiments, enabling a direct comparison to the scheduled experiments.
Keywords: electrical resistivity; magneto-hydro-dynamic simulations; optically thin radiative losses; plasma dynamics; Radiation Transport; X-pinch